2009
DOI: 10.1152/ajprenal.00146.2009
|View full text |Cite
|
Sign up to set email alerts
|

20-HETE activates the Raf/MEK/ERK pathway in renal epithelial cells through an EGFR- and c-Src-dependent mechanism

Abstract: Hydroxyeicosatetraenoic acid (20-HETE) has been reported to promote mitogenicity in a variety of cell types, including renal epithelial cells. However, the signal transduction pathways activated by 20-HETE have not been fully defined. The present study evaluated the effects of 20-HETE and its more stable agonist analogs 20-hydroxyeicosa-5(Z),14(Z)-dienoic acid (5, and N- [20-hydroxyeicosa-5(Z),14(Z)-dienoyl]glycine (5,14-20-HEDGE) on the Raf/MEK/ERK and phosphatidylinositol 3-kinase (PI3K)-Akt pathway in LLC-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 50 publications
2
40
0
Order By: Relevance
“…Kidney tissue was homogenized in 1X radioimmunoprecipitation assay buffer (Millipore, Billerica, MA) with protease and phosphatase inhibitors (Pierce Biotechnology, Rockford, IL), and protein lysates were isolated after differential centrifugation. Immunoblot analysis was performed as previous published (Akbulut et al, 2009;Nadella et al, 2010;Regner et al, 2011;Kwon et al, 2012). In brief, protein lysates (25 mg) were size separated on a 4-12% NuPAGE Bis-Tris Gradient Gel (Life Technologies) and were subsequently transferred to a supported polyvinylidene difluoride membrane (Bio-Rad Laboratories, Hercules, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Kidney tissue was homogenized in 1X radioimmunoprecipitation assay buffer (Millipore, Billerica, MA) with protease and phosphatase inhibitors (Pierce Biotechnology, Rockford, IL), and protein lysates were isolated after differential centrifugation. Immunoblot analysis was performed as previous published (Akbulut et al, 2009;Nadella et al, 2010;Regner et al, 2011;Kwon et al, 2012). In brief, protein lysates (25 mg) were size separated on a 4-12% NuPAGE Bis-Tris Gradient Gel (Life Technologies) and were subsequently transferred to a supported polyvinylidene difluoride membrane (Bio-Rad Laboratories, Hercules, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Such hypothesis has been postulated for the mitogenic action of 20-HETE in renal epithelial cells. Akbulut et al (2009) showed that 20-HETE activates the Raf/MAPK kinase/extracellular signal-regulated kinase pathway in renal epithelial cells through an EGFR-and c-Src-dependent mechanism and proposed the presence of a 20-HETEspecific G-protein coupled receptor-EGFR transactivation through c-Src. To date, a receptor/binding site for 20-HETE has been implicated based on the use of specific agonists and antagonists, but it still needs to be identified.…”
Section: -Hete Induces Ace Expression Via Nf-kb Bindingmentioning
confidence: 99%
“…The proximal tubular cell proliferative response to epidermal growth factor (EGF) is associated with increased 20-HETE synthesis (113). CYP hydroxylase inhibitors attenuate the rat proximal tubule cell proliferative response to EGF (1). Signal transduction pathways were evaluated in a well-characterized porcine proximal tubule cell line, LLC-PK1.…”
Section: Proximal Tubular Transportmentioning
confidence: 99%
“…Signal transduction pathways were evaluated in a well-characterized porcine proximal tubule cell line, LLC-PK1. 20-HETE and 20-HETE analogs activate the Raf/MEK/ERK and Akt pathways in LLC-PK1 cells (1). Activation of these pathways by 20-HETE was secondary to the activation of c-Src and EGF receptor (1).…”
Section: Proximal Tubular Transportmentioning
confidence: 99%